GEOSPATIAL MODELING AS A METHOD FOR FORECASTING OIL-PROSPECTIVE HORIZONS IN THE SECTION OF THE EARTH`S CRUST - Sh. Zhantayev, Zh.; Bibosinov, A.Zh.; Iskakov, B.A.; Fremd, A.G. (Academic Scientific Journal of Computer Science, 2020)
Modern ideas about the formation of hydrocarbon deposits are based on the results of experimental and theoretical studies of the dynamics of the lithosphere. They are based on the established facts of “instability of fluid systems in the sedimentary cover and basement, as well as migration of fluids through permeable zones resulting from changing stresses in the earth's crust. It follows from this that the geological environment is nonequilibrium. Forces of external action and thermodynamic conditions inside the crust contribute to the extrusion of fluids from the lower horizons to the upper and ensure their movement through the zones of decompression to the places of unloading, which are often fracture zones limited by fluid resistances. And this means that the centers of unloading are not static, but replenished and the process of formation of deposits is essentially geodynamic. Thus, one of the factors for successfully predicting the oil prospectivity of the study area is the detection and analysis of the morphological features of the weakened zones, which are usually not only faults, but also horizons, which are layers that differ from the host rocks by a relatively high coefficient of porosity and fracture and can serve collectors. As well as adjacent multidirectional formations, essentially representing subvertical channels providing the flow of hydrocarbons into the reservoir. On the other hand, it is of interest to visualize the section of the geological environment from the standpoint of geomechanical permeability, an indicator of which can be the distribution of the horizontal component of the low lithostatic pressure. Visualization of the distribution of the stresses that are responsible for possible horizontal fluid movements allows us to differentiate the section from the standpoint of the geometry and intensity of the weakened zones and the possible migration routes of fluids, including hydrocarbons, associated with them. Obviously, such model constructions will make it possible to draw non-trivial conclusions about the nature of the known reservoir and use this methodological approach in predicting the locations of other possible hydrocarbon accumulations. In the present work, using the example of a well-known hydrocarbon field, we consider the methodology and the results of parametric modeling of the geological environment – creating a three-dimensional image of the distribution of decompression zones and stress-strain state (SSS) parameters using data previously performed on this area of seismic studies using the common depth point method (MOGT) .. Presentation of seismic data in the decompression parameters, reinforced by the SSS parameters, makes it possible to obtain a “formalized” section and thereby increase the efficiency of geophysical surveys both at the search stage and at the stage of exploitation of hydrocarbon deposits.